Chromogenic Agar Medium : A Versatile Tool for the Diagnosis of UTI - Nahar, S Gul; Hasan, M Bulbul; Khatun, Mst Rokeya; Ali, M Nawshad; Mohanta, DK (TAJ: Journal of Teachers Association, 2018)
Objective: The present study was done on Chromogenic agar media to identify uropathogens more efficiently by its characteristic colony colour for each of the organism. Methodology: A total 300 sample were collected from Rajshahi Medical College Hospital, Bangladesh. Urine samples of the suspected UTI cases, showing pus cells >5/HPF on microscopic examination were included for urine culture simultaneously onto Chromogenic agar media, Blood agar and MacConkey agar media. Results: Culture yielded 139 (46.33%) bacterial growth among them, 133 (44.33%) showed single organism and remaining 06 (2.00%) showed mixed growth of two organisms in different combinations. It is evident from the present study that both Chromogenic agar media and Blood agar (BA) media supported growth of all 145 bacteria, while MacConkey (MAC) agar yielded 133(91.72%) bacterial growths. The rate of presumptive identification of the isolates was found significantly higher (97.24%) on Chromogenic agar media when compared with the MacConkey agar (80.68%) and Blood agar (27.58%) media. Out of 91 E. coli isolated, 88(96.70%) could be identified differentially on Chromogenic agar media in contrast to 85(93.40%) on MacConkey agar and only 06(06.59%) on Blood agar. Again, all 06 (100%) of the isolate-pairs of mixed growth were identified distinctly on Chromogenic agar media, whereas both Blood agar and MacConkey agar media could revealed only 01(16.66%) of the polymicrobial growth. Conclusion: Chromogenic agar media has been documented for its very high yielding rate, rapid presumptive identification of both single and polymicrobial growths with greater precision and avoidance of biochemical tests for further identification of uropathogens. Thus it can be recommended as primary urine culture medium to be used by the clinical microbiology laboratories. TAJ 2012; 25: 64-71